2022
DOI: 10.1002/cjoc.202200147
|View full text |Cite
|
Sign up to set email alerts
|

Morphology‐Dependent Catalysis of CeO2‐Based Nanocrystal Model Catalysts

Abstract: Comprehensive Summary Recent progress in colloidal synthesis has realized the preparations of uniform nanocrystal (NC) model catalysts with rich and well‐controlled morphologies that were employed to explore structure‐activity relationships of powder catalysts, similar to single‐crystal‐based model catalysts under ultrahigh vacuum conditions but can work at the same conditions as powder catalysts without the “materials gap” and “pressure gap”. In this perspective, the CeO2‐based NC model catalysts with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 136 publications
(211 reference statements)
1
9
0
Order By: Relevance
“…According to Wulff’s rule, c-CeO 2 NCs with highly symmetric cubic morphologies are enclosed with {100} crystal planes. However, the {111} crystal planes are predominantly exposed on p-CeO 2 with irregular shapes, as evidenced by previous literature. It could be controversial on the exposed crystal planes of r-CeO 2 NCs with less symmetric morphologies that depend on the preparation parameters such as the calcination temperature. , Based on previous detailed characterizations, it could be concluded that r-CeO 2 NCs calcined at 500 °C are mainly enclosed with both the {110} facets (top, bottom, and side) and the {100} facets (side). The Ce 3d XPS spectra together with vis- and UV-Raman spectra (Figure S2) clearly demonstrate both the total and the surface oxygen vacancy concentrations following the order r-CeO 2 > c-CeO 2 > p-CeO 2 , consistent with previous results. , …”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…According to Wulff’s rule, c-CeO 2 NCs with highly symmetric cubic morphologies are enclosed with {100} crystal planes. However, the {111} crystal planes are predominantly exposed on p-CeO 2 with irregular shapes, as evidenced by previous literature. It could be controversial on the exposed crystal planes of r-CeO 2 NCs with less symmetric morphologies that depend on the preparation parameters such as the calcination temperature. , Based on previous detailed characterizations, it could be concluded that r-CeO 2 NCs calcined at 500 °C are mainly enclosed with both the {110} facets (top, bottom, and side) and the {100} facets (side). The Ce 3d XPS spectra together with vis- and UV-Raman spectra (Figure S2) clearly demonstrate both the total and the surface oxygen vacancy concentrations following the order r-CeO 2 > c-CeO 2 > p-CeO 2 , consistent with previous results. , …”
Section: Resultsmentioning
confidence: 66%
“…Second, the oxygen vacancy concentrations were qualitatively compared on the basis of the Raman and Ce 3d XPS spectra. In the Raman spectra (Figure C,D), two vibrational bands at around 465 and 593 cm –1 were observed, typically assignable to the F 2g and defect-induced mode (D) of the cubic fluorite CeO 2 phase, respectively. , It is noteworthy that the I D / I F2g values in both the vis-Raman (Figure C) and the UV-Raman (Figure D) spectra, respectively, used to evaluate the total and surface oxygen vacancy concentrations, follow the order 2%Rh/r-CeO 2 > 2%Rh/c-CeO 2 ≫ 2%Rh/p-CeO 2 . This indicates that the oxygen vacancy concentrations over the 2%Rh/r-CeO 2 catalyst are always higher than those over 2%Rh/c-CeO 2 and 2%Rh/p-CeO 2 catalysts, consistent with the orders of pristine CeO 2 supports (Figure S2).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Among various metal oxides, the regulation of surface properties of CeO 2 has been widely explored for many important heterogeneous catalysts due to its reversible Ce 3+ /Ce 4+ redox pair associated with the tailorable structural defects of oxygen vacancy. The rich surface chemistry of CeO 2 including Lewis acidic site, Lewis basic site, Bronsted acidic site, and oxygen vacancy provides an ideal platform to understand the significant influence of adsorption behavior on catalytic performance of CeO 2 -based heterogeneous catalysts. The regulation of surface properties of CeO 2 -based catalysts and their catalytic applications have been well summarized and illustrated in previous reviews. ,,, …”
Section: Introductionmentioning
confidence: 99%